PENCEMARAN NAMA BAIK MELALUI MEDI ELEKTRONIK DALAM PRESPEKTIF PUTUSAN PENGADILAN NOMOR 450/Pid.Sus/2017/PN.Smr TENTANG PENCEMARAN NAMA BAIK - Padli Padli (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACTDefamation is also known as insult, which is basically attacking the good name and honor of someone who is not in a sexual sense so that the person feels wronged. Honor and good name have different meanings, but they cannot be separated from one another, because attacking honor will result in tarnished honor and good name, as well as attacking a good name will result in a person's good name and honor can be tainted.This type of research is included in the writing of normative law through a statutory approach.The results of this determination explain that the legal arrangements for defamation through electronic media have been regulated in article 27 paragraph (3) of law number 11 of 2008 concerning electronic information and transactions which reads: "Everyone knowingly and without the right to distribute and / or transmit and / or make accessible electronic information and / or electronic documents that contain defamatory and / or defamation ”. The threats obtained from criminal defamation through electronic media are regulated in Article 45 paragraph (3) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions, with the threat of imprisonment. a maximum of 4 (four) years and / or a fine of not more than IDR 750,000,000.00 (seven hundred and fifty million rupiahs). The application of the law against defamation through electronic media in the perspective of court decisions number 450 / Pid.Sus. / 2017 / PN.Smr regarding defamation is by taking legal channels, namely the judiciary.  Keywords: Defamation, Electronic Media, Crime